Introduction to steels processing, properties, and applications - Angelo, P. C.; Ravisankar, B. (Boca Raton, FL : CRC Press/Taylor & Francis Group, 2019)
"The book briefly describes the structure, properties and applications of various grades of steel, covering most of the important types of steels including iron-carbon diagram, heat treatment, surface hardening methods, effect of alloying, specific applications, selection of materials, case studies and so forth"--
OCLC-licensed vendor bibliographic record.
Keywords: Steel -- Metallurgy; TECHNOLOGY & ENGINEERING / Metallurgy; TECHNOLOGY / Material Science; TECHNOLOGY / Metallurgy; TECHNOLOGY / Engineering / Chemical & Biochemical